Greece : Fifth Review Under the Stand-By Arrangement, Rephasing and Request for Waivers of Nonobservance of Performance Criteria; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2011)
The Executive Board of the IMF has completed the fifth review of Greece's economic performance under a program supported by a three-year Stand-By Arrangement (SBA) for the country. The completion of the review enables the immediate disbursement of an amount equivalent to SDR1.9 billion, bringing total IMF disbursements under the SBA to an amount equivalent to SDR 17.5 billion. The creation of a national unity government and the endorsement of program objectives and policies by major parties is an important step.